Benthic Response to Flow Alteration in a New Mexico Arid Mountain Stream†. (2nd February 2016) - Wiseman, C.; Marotz, B.; Caldwell, J.; Sherrick, R.; Ward, D.
Abstract: Past and current pressure on streams and rivers for consumptive use requires the development of tools and decision‐making processes for water managers to minimize impacts on ecological function. This paper examines the utility of modeling benthic biomass in relation to benthic macroinvertebrate (BMI) community attributes for water resource management scenarios in the Cliff‐Gila Valley of the Gila River, New Mexico, USA. The river benthos biomass model (RivBio) was used in conjunction with hydraulic modeling to predict growth and decline of benthic biomass. BMI community attributes were compared along gradients of hydrologic impact (successive existing diversions) in the Cliff Gila Valley and were compared to community attributes in similar regional streams. Benthic biomass was minimally affected by proposed diversions at flows above 4.25 cms (150 cfs), but was severely reduced downstream because of existing diversions during lower flow periods. Riffle habitat was disproportionately affected during extreme low and interrupted flow, which may have resulted in BMI communities shifted towards multi‐habitat generalists that can persist in lentic conditions. Flow augmentation from proposed diversions and storage would greatly mitigate these existing biomass losses by providing consistent base flow and lotic conditions in riffle habitat. Both benthic biomass and BMI community endpoints were useful when comparing water management scenarios. Copyright © 2016 John Wiley & Sons, Ltd.